1997
DOI: 10.1105/tpc.9.8.1289
|View full text |Cite
|
Sign up to set email alerts
|

A gene fusion at a homeobox locus: alterations in leaf shape and implications for morphological evolution.

Abstract: Compound leaves are seen in many angiosperm genera and are thought to be either fundamentally different from simple leaves or elaborations of simple leaves. The knottedl-like homeobox (knox) genes are known to regulate plant development. When overexpressed in homologous or heterologous species, this family of genes can cause changes in leaf morphology, including excessive leaf compounding in tomato. We describe here an instance of a spontaneously arisen fusion between a gene encoding a metabolic enzyme and a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(62 citation statements)
references
References 38 publications
2
59
0
1
Order By: Relevance
“…Among the best studied of these are the MADS-box family of genes that control floral-organ identity (Pnueli et al 1991(Pnueli et al , 1994a and the knotted1-like homeobox (KNOXI) genes that regulate leaf morphogenesis (Avivi et al 2000;Janssen et al 1998;Chen et al 1997;Parnis et al 1997;Hareven et al 1996). Moreover, a large number of loci affecting vegetative and floral morphology have been identified through mutant analysis (Stevens and Rick 1986).…”
Section: Correspondence Of Qtl To Known Mutant Loci In Tomatomentioning
confidence: 99%
“…Among the best studied of these are the MADS-box family of genes that control floral-organ identity (Pnueli et al 1991(Pnueli et al , 1994a and the knotted1-like homeobox (KNOXI) genes that regulate leaf morphogenesis (Avivi et al 2000;Janssen et al 1998;Chen et al 1997;Parnis et al 1997;Hareven et al 1996). Moreover, a large number of loci affecting vegetative and floral morphology have been identified through mutant analysis (Stevens and Rick 1986).…”
Section: Correspondence Of Qtl To Known Mutant Loci In Tomatomentioning
confidence: 99%
“…This antagonistic relationship is characteristic of many plants with simple leaves (Waites et al 1998;Byrne et al 2002), but has been shown to break down in plants with compound leaves. In these, ARP and KNOX1 genes are either co-expressed in leaf primordia (Cardamine hirsuta; Hay and Tsiantis 2006) or in the SAM and leaf primordia (Solanum lycopersicum; Hareven et al 1996;Chen et al 1997;Koltai and Bird 2000).…”
Section: Communicated By K Schneitzmentioning
confidence: 99%
“…However, repression of knox genes in leaves is not necessarily a prerequisite for proper leaf development as there are exceptions to this rule. In tomato, natural leaf expression of knox genes correlates with leaf dissection (Chen et al 1997). In barley, ectopic knox expression causes no leaf phenotype but flower phenotypes (Mu¨ller et al 1995(Mu¨ller et al , 2001.…”
Section: Introductionmentioning
confidence: 99%